A cross-sectional study in a tertiary care hospital in China: noise or silence in the operating room. Issue 9 (18th September 2017) - Wang, Xiaoxiao; Zeng, Lin; Li, Gang; Xu, Mao; Wei, Bin; Li, Yan; Li, Nan; Tao, Liyuan; Zhang, Hua; Guo, Xiangyang; Zhao, Yiming
Abstract : Objectives: This study aims to provide a comprehensive description of noise levels in operating rooms (ORs) in a tertiary care hospital in China. Additionally, the study aims to examine the deviation in noise levels from international and internal standards as well as the differences in noise levels by category of surgery and day of the week. Methods: We monitored noise levels in 23 ORs in a tertiary care hospital in China between August 2015 and March 2016. Dosimeters were used to determine noise levels. The noise data collected in the dosimeter were downloaded to an IBM computer for subsequent analysis. One-way analysis of variance and Student's t-test were used to examine the differences in noise levels. Results: The noise level in the ORs ranged between 59.2 and 72.3 dB(A), with 100% of the measurements exceeding the recommended hospital noise standards. There was substantial similarity in noise levels from Monday to Friday (F=1.404, p=0.234), with a range between 63.7 and 64.5 dB(A). The difference in noise levels by category of surgery was significant (F=3.381, p<0.001). The results of the post hoc analysis suggested that ophthalmic surgery had significantly higher noise levels than otolaryngological surgery or general surgery. Conclusions: Ophthalmic surgery had significantly higher noise levels than otolaryngological or general surgeries. High noise levels were identified in all evaluated ORs during weekdays, and these levels consistently exceeded the currently accepted standards. These findings warrant further investigation to determine the harmful effects of noise on both patients and staff in ORs.￼￼